Ayurvedic Life Style Drugs Promise Blissful Life - Dimri, Mayank; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
Holistic health concept of ayurveda formulated polyactive pharmacons of life style drugs for regenerating the natural physicological order. They eradicate disorders caused by addictive and subjective life styles of poor quality.